Essay: Linking Keynesian Theory to Economic Geography - Ahn, Young-Jin; Juraev, Zuhriddin (Future Science / FSH-PH Publications, 2023)
This article examines the application of Keynesian theory in the field of economic geography, with a specific focus on regional development and the reduction of inequalities. The objective is to emphasize the importance and advantages of applying Keynesian principles to address spatial economic challenges. The novelty lies in examining the intersection of Keynesian economics and geography, which provides insights into regional planning, infrastructure development, and cluster formation. The results demonstrate how policymakers and researchers can utilize Keynesian theory to foster balanced growth and enhance living standards. The keywords for this article are Keynesian theory, economic geography, regional development, disparities, and policy interventions.